FEATURES OF PSYCHOLOGICAL REHABILITATION OF WOUNDED SERVICEMEN IN THE POST-WAR PERIOD - Mkrtumyan, Mels; Mkrtumyan, Lilit (Modern Psychology, 2024)
The article discusses the peculiarities of changes in the psychophysiological characteristics of the post-traumatic states of the servicemen wounded in the Artsakh War of 2020 in the post-war period. In the process of special accompanying and rehabilitation work, depending on the nature of physical and mental trauma, negative factors accumulated in the course of past military battles, characteristics of individual experiences and methods of individual control and assessment of general and mental health were identified. Depending on the nature of the injury (lower or upper extremities), their psychophysiological consequences, specific personal experiences, as well as socio-psychological features of interpersonal communication were differentiated. Thanks to the unique complex of psychorehabilitation, the functional capabilities of the body of servicemen were activated in special sessions, the process of self-regulation of subjective sensations and experiences was optimized. In parallel, special physiotherapy exercises were conducted, which contribute to self-organization, management and coordination of motor capabilities, as well as ensuring an optimal level of general and mental health of military personnel.